Advances in simultaneous atmospheric profile and cloud parameter regression based retrieval from high‐spectral resolution radiance measurements. Issue 12 (19th June 2013) - Weisz, Elisabeth; Smith, William L.; Smith, Nadia
Abstract : [1] The dual‐regression (DR) method retrieves information about the Earth surface and vertical atmospheric conditions from measurements made by any high‐spectral resolution infrared sounder in space. The retrieved information includes temperature and atmospheric gases (such as water vapor, ozone, and carbon species) as well as surface and cloud top parameters. The algorithm was designed to produce a high‐quality product with low latency and has been demonstrated to yield accurate results in real‐time environments. The speed of the retrieval is achieved through linear regression, while accuracy is achieved through a series of classification schemes and decision‐making steps. These steps are necessary to account for the nonlinearity of hyperspectral retrievals. In this work, we detail the key steps that have been developed in the DR method to advance accuracy in the retrieval of nonlinear parameters, specifically cloud top pressure. The steps and their impact on retrieval results are discussed in‐depth and illustrated through relevant case studies. In addition to discussing and demonstrating advances made in addressing nonlinearity in a linear geophysical retrieval method, advances toward multi‐instrument geophysical analysis by applying the DR to three different operational sounders in polar orbit are also noted. For any area on the globe, the DR method achieves consistent accuracy and precision, making it potentially very valuable to both the meteorological and environmental user communities. Key Points: Dual‐regression provides reliable parameters from high‐spectral radiances. Works with any polar‐orbiting sounder (AIRS, IASI or CrIS). Retrieved cloud heights compare very well with cloud heights from CALIOP.